International trade effects of student migration - Lena Susanne Specht (University College Dublin, UCD School of Economics, 2022)
The conventional immigration and trade literature regards immigrants as mediators for informal barriers such as institutional and cultural differences. However, this notion neglects network effects stemming from short visits. This paper investigates the ways in which international student migration relates to trade. Unlike other immigrants, international students make a special case because of their short stay and high education level. Leveraging panel data on 34 mostly OECD host countries and 172 origin countries between 2000 and 2018, I employ a gravity-type trade model to examine this relationship. I find that overall immigration contributes to trade and international students particularly increase their host countries' exports to their origin country. Further results suggest that the student effect varies by country and product. While their ability to foster the most information-intensive trades is limited relative to the average immigrant, international students have an advantage in promoting trust between institutionally distant countries.
Keywords: F12; F14; F22; 330; International trade; International students; Networks; Migration; Gravity model